Association of uveitis with pediatric autoimmune diseases based on a TriNetX study - Alan Y. Hsu; Hou-Ting Kuo; Chun-Ju Lin; Chang-Ching Wei; Ning-Yi Hsia; James Cheng-Chung Wei; Yu-Hsun Wang; You-Ling Li; Chun-Ting Lai; Huan-Sheng Chen; Yi-Yu Tsai (Scientific Reports)
Abstract To investigate for the risk of uveitis among such patients. A retrospective cohort study utilized the TriNetX database and recruited pediatric autoimmune patients diagnosed between January 1st 2004 and December 31st 2022. The non-autoimmune cohort were randomly selected control patients matched by sex, age, and index year. The main outcome is the incidence of new-onset uveitis. 175,328 pediatric patients with autoimmune diseases (mean age 10.7 +/- 5.1 years; 55.8% female; 66.2% White) and 175,328 pediatric patients without autoimmune diseases (mean age 10.8+/- 5.1 years; 55.7% female; 66% White) were recruited. The autoimmune cohort demonstrated a significantly increased uveitis risk across our 18-year study period (HR 4.42 [95% CI 3.98–4.90]). Iridocyclitis, chorioretinal inflammation, unspecified purulent endophthalmitis, panuveitis, retinal vasculitis, and sympathetic uveitis were uveitis conditions significantly associated with autoimmune diseases. Autoimmune patients who had used immunosuppressant medications had increased uveitis risk compared to those who had never used immunosuppressants. Our subgroup analysis also demonstrated a significantly increased uveitis risk associated with specific autoimmune conditions. Conditions include inflammatory arthritis, systemic autoimmune rheumatic diseases, systemic vasculitis, inflammatory bowel disease, psoriasis, multiple sclerosis, and immune thrombocytopenic purpura. Using hazard ratios HR for comparison, we were able to identify that, out of the previously broadly defined category of autoimmune diseases, only these specific conditions were significantly associated with pediatric uveitis. Uveitis was significantly associated with autoimmune diseases among the pediatric population.